Experiences with archived raw diffraction images data: capturing cisplatin after chemical conversion of carboplatin in high salt conditions for a protein crystal - Tanley, S.W.M.; Diederichs, K.; Kroon-Batenburg, L.M.J.; Schreurs, A.M.M.; Helliwell, J.R. (International Union of Crystallography, 2013)
The archiving of raw diffraction images data is the focus of an IUCr Diffraction Data Deposition Working Group (see http://forums.iucr.org/). Experience in archiving and sharing of raw diffraction images data in collaboration between Manchester and Utrecht Universities, studying the binding of the important anti-cancer agents, cisplatin and carboplatin to histidine in a protein, has recently been published. Subsequently, these studies have been expanded due to further analyses of each data set of raw diffraction images using the diffraction data processing program XDS. The raw diffraction images, measured at Manchester University, are available for download at Utrecht University and now also mirrored at the Tardis Raw Diffraction Data Archive in Australia. Thus a direct comparison of processed diffraction and derived protein model data from XDS with the published results has been made. The issue of conversion of carboplatin to cisplatin under a high chloride salt concentration has been taken up and a detailed crystallographic assessment is provided. Overall, these new structural chemistry research results are presented followed by a short summary of developing raw data archiving policy and practicalities as well as documenting the challenge of making appropriate and detailed recording of the metadata for crystallography.
Keywords: SDG 3 - Good Health and Well-being